The Use of Facebook to Improve Students` Skill and Increase Their Motivation in Writing Recount Text - Khusnita, Dafi (Universitas Muhammadiyah Semarang, 2017)
This article is about the use of Facebook as learning recount texts media to improve the writing skill and increase motivation of tenth grade students of SMA N 1 Kajen, in the academic year of 2012/2013. It aimed to investigate the way Facebook improved students skill and increased their motivation in writing recount texts. It adopted an action research design which was carried out through pre-test, cycle 1, and cycle 2. The subjects of the research were 32 students of X 2 class of SMA N 1 Kajen. A Facebook group was created as a place for students to write recount texts as well as to give feedback to their peers writings. Writing tests, observation sheet, and questionnaire were used as the instruments of collecting the data. The results of the writing tests at the end of the three cycles showed a significant improvement of the students writing. The result of the observation showed that after learning writing recount text using Facebook, the students became more attentive, active, and attracted in joining the lesson; and happier and more serious in writing. The analysis of the questionnaire showed that the students responded the use of Facebook in their learning positively. Based on the overall results of the research, it can be concluded that the use of Facebook contributes to the improvement of students skill and motivation in writing recount texts.